STRATEGI PENGEMBANGAN KEPERCAYAAN DIRI PADA ANAK USIA DINI - Fitriani, Amilah (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2010)
Basically, early childhood is a social creature and not miniature adults, where children will learn to communicate and interact with the environment around him. Provision of opportunities, learn to respect the child, parenting, and the reward can help children to build confidence and self-esteem so that children can interact and communicate well with the surrounding environment.